Optimalisasi Sistem Perawatan pada Tumbler Drayer dengan Metode RCM di Hotel X - Fadlan, Muhammad; Mukhnizar, Mukhnizar; Selviyanty, Veny; Abu, Risal; Afdal, Afdal (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Reliability Centered Maintenance (RCM) is a process to determine effective maintenance. Dryer Tumbler is a drying machine that has a concentrated air flow pattern and a sealed cylinder rim to ensure the water management system works optimally. This tool is very useful and beneficial especially for laundry because it can produce the highest output in meeting the workload. Repeated component damage occurs in the dryer tumbler machine at Hotel X due to less than optimal maintenance. This is because the maintenance and repair estimates for the existing dryer tumbler machine have not been managed with good and suitable methods. Repeated component interference in the machine makes the machine's performance less than optimal, thus hampering the production process. The production process that is not running optimally causes the resulting product to also experience a decrease in quality. Based on the calculation of component replacement costs, cost savings of 85.17% were obtained for dryer bearings, 2.84% for flatbelts, 58.59% for sizepress bearings and 75.23% for gear couplings.